Detection of Helicobacter pylori using non-invasive techniques in Duhok City, Iraq - Reem Polse; Haliz Hasan; Haval Khalid; Wijdan Mero (The Egyptian Journal of Internal Medicine)
Abstract Background Helicobacter pylori infection affects over 50% of the global population. Individuals acquire this infection in early childhood that persists throughout life if not treated. The degree of the outbreak severity varied from one region to another, causing long-term clinical consequences such as gastritis, peptic ulcer disease, and cancer of the stomach. The primary objective of this investigation was to estimate the prevalence of Helicobacter pylori among the population in Duhok City via the implementation of non-invasive methods. Methods From January 2021 to December 2022, 2313 cases were studied using ELISA assays for immunoglobulins, IgG, IgM, and IgA, a stool antigen test (SAT), and a urea breath test (UBT) to identify Helicobacter pylori. Results Among 2313 patients of both genders, 61.7% (1427/2313) were females and 38.3% (886/2313) were males. The prevalence of H. pylori infection was 35.28% among them, with a high significant difference in infection rate in females than males (60.78% vs 39.22%), and among various ages with the highest being at ages of 31 to 40 years. The serological and the SAT tests are commonly used diagnostic tests that yield the most significant number of positive results. Furthermore, a notable correlation was observed between the prevalence of infection and age, especially for IgA and UBT where males exhibited higher significant levels than females; moreover, for UBT, highly significant variations were observed among ages also. Conclusions Over half of the performed tests detected H. pylori antibodies with the peak at 49.3% for the IgG test, indicating the body elicits an immune response against this bacterium. Both gender and age were linked to this infection. For more clarification of the prevalence of H. pylori, we recommend conducting more in-depth investigations.